2008
DOI: 10.1007/s11262-007-0196-7
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and phylogenetic analysis of membrane protein genes of porcine epidemic diarrhea virus isolates in China

Abstract: Six porcine epidemic diarrhea viruses (PEDVs) were isolated from the fecal samples of piglets infected with PEDV in 2006 in China. The membrane (M) protein genes of six PEDV isolates were amplified by reverse transcriptase-polymerase chain reaction (RT-PCR), then cloned, sequenced, and compared with each other as well as those ten PEDV reference strains. The M protein genes of six Chinese PEDV isolates consisted of 692 nucleotides containing a single open reading frame (ORF) of 681 nucleotides, which encoded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 20 publications
1
69
0
Order By: Relevance
“…In 2006, an analysis of the M gene of 6 PEDVs isolated from the faeces of Chinese piglets indicated that the isolates compose a separate cluster with Chinese strain JS-2004-02 [60]. These results demonstrated that there may be a new prevailing PEDV genotype in China [60].…”
Section: Molecular Epidemiology Of Pedvmentioning
confidence: 98%
“…In 2006, an analysis of the M gene of 6 PEDVs isolated from the faeces of Chinese piglets indicated that the isolates compose a separate cluster with Chinese strain JS-2004-02 [60]. These results demonstrated that there may be a new prevailing PEDV genotype in China [60].…”
Section: Molecular Epidemiology Of Pedvmentioning
confidence: 98%
“…At present, PED has been a major concern in the swine industry, particularly, in the Asia and Europe, resulting in large economic losses [2][3][4]. The causative agent of PED is porcine epidemic diarrhea virus (PEDV), an enveloped and single-stranded RNA virus that belongs to the family Coronaviridae [5].…”
Section: Introductionmentioning
confidence: 99%
“…These fecal samples were confirmed to be positive for TGEV using the Anigen Rapid TGE Ag Test Kit (Animal Genetics Inc.). TGEV-positive fecal samples were handled as described previously [31]. The supernatants were collected for the amplification of the N gene by RT-PCR.…”
Section: Tgev Samplesmentioning
confidence: 99%
“…A negative control was always included. The specificity of the PCR was evaluated using other common viral causative agents of diarrhea: porcine epidemic diarrhea virus (PEDV) and porcine rotavirus and the PCR oligonucleotides used to amplify bands were as described previously [31,32].…”
Section: Rt-pcr Amplification and Rflp Analysismentioning
confidence: 99%